Cryogenic-based CO2 capture technologies: State-of-the-art developments and current challenges. (March 2019) - Song, Chunfeng; Liu, Qingling; Deng, Shuai; Li, Hailong; Kitamura, Yutaka
Abstract: CO2 capture, utilization and storage has been recognized as a primary option to mitigate the issue of climate change caused by the utilization of fossil fuels. Several CO2 capture strategies have been developed, such as absorption, adsorption, membrane, chemical looping, hydrating and biofixation. Among different technologies, particular attention has been given to cryogenic CO2 capture by phase change. The aim of this study is to improve interest in cryogenic technologies for CO2 capture by providing an overview of the actual status of CCS. To reach this goal, the major strategies and technologies for CO2 capture from fossil fuel combustion have been reviewed. Simultaneously, the characteristics of cryogenic technologies for CO2 capture are summarized. The existing challenges that need to be overcome in cryogenic technology include cold energy sources, capture costs and impurities, etc. Finally, opportunities for the future development of cryogenic-based technologies are discussed. The results of this investigation indicated that cryogenic CO2 capture processes can be easily retrofitted to the existing industrial emission facilities and avoid the challenges associated with chemical solvents or physical sorbents. Highlights: Challenges of existing CO2 capture processes are summarized. Developments of cryogenic-based CO2 capture processes are reviewed. Potential advantages and challenges of cryogenic-based CO2 capture processes are discussed. Intensification strategies for cryogenic-based CO2 capture processes are proposed.